Growth response of corn due to application of simple mixed compound fertilizer derived from urea - azolla (azolla sp.) - coal fly ash - Hermawan, Agus; Budianta, Dedik; Warsito (Journal of Smart Agriculture and Environmental Technology, 2023)
Mixing urea with natural materials that can reduce the rate of urea dissolution is known to increase the N availability replenished by inorganic fertilizers which absorbed by plants for growth and production.This study aimed to examine the effective of application of pellet N fertilizer prepared by coal fly ash- azolla and urea on the response of corn planted in acidic Ultisol. This pot experiment was performed in the greenhouse and soil analysis was conducted in the Laboratory of Chemistry, Biology and Soil Fertility, Soil Science Department, Faculty of Agriculture, Sriwijaya University. The research was arranged using a completely randomized design with nine treatments and three replications. The treatments applied were a mixed composition materials (w/w) of 50% coal fly ash + 50% azolla, and 40% coal fly ash + 60% azolla respectively. Each composition (w/w) of 70% coal fly ash- Azolla mixture was then incorporated by 30% urea and compacted as pellets using a manual screw extruder. In addition, to compare the effect of pellet, it was done the other treatment by granular urea fertilizer only applied by immersing and sowing on the soil surface. The results showed that the application of N slow release using the pellet forms significantly increased N availability, plant N uptake, plant height and dry weight of corn. The N slow release as a pellet can reduce the dose of N inorganic fertilizer as urea by 25%. The response of corn at a dose of 0.75 times is not significantly different from the dose of 1 times the recommended dose of N.